Functional dependencies for XML - Ahmad, Kamsuriah; Mamat, Ali; Ibrahim, Hamidah; Mohd Noah, Shahrul Azman (2007)
In relational the concept of functional dependencies is well established and was used in integrity enforcement and in database design. Functional dependencies were used to specify the constraints and discover data redundancies that may exist in the relations. As the number of applications using native XML documents is increasing rapidly there exists a great interest how to extend this concept to XML world. However generalizing relational constraints to XML constraints is nontrivial because of the hierarchical and flexible structure of XML compared with flat representation of relational table. In this paper we propose a formal definition of functional dependencies for XML that can specify constraints in hierarchical structure of XML. The advantage of this definition is that they are able to specify constraints that hold not only in the entire document but also can scope within the sub-document.